Soft X-ray diffraction patterns measured by a LiF detector with sub-micrometre resolution and an ultimate dynamic range; Journal of Synchrotron Radiation; Vol. 27, iss. 3 - Makarov S. Sergey; Pikuz S. Sergey; Ryazantsev S. Sergey; Pikuz T. Tatiana; Buzmakov A. Alexey; Rose M. Max; Lazarev S. V. Sergey Vladimirovich; Senkbeil T. Tobias; Von Gundlach A. Andreas; Stuhr S. Susan; Rumancev C. Christoph; Dzhigaev D. Dmitry; et al. (2020, 2020)
Title screen